A new species of the genus Tachydromia Meigen from Europe (Diptera: Empididae). - Chvála, Milan (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The author describes a new European Tachydromia species of the cursitans-pallidiventris-group (apud Collin, 1961). Nomenclatural Acts collini Chvála, 1965 (Tachydromia), spec. n.